Understanding the pharmacokinetic journey of Fc-fusion protein, rhIL-7-hyFc using complementary approach of two analytical methods, accelerator mass spectrometry and ELISA - Kim, Anhye; Oh, Min-Seok; Lee, Gwan-Ho; Song, Seongeun; Byun, Mi-sun; Choi, Donghoon; Yu, Byung-Yong; Lee, Howard (Oxford University Press, 2024)
Antibody-based therapeutics (ABTs), including monoclonal/polyclonal antibodies and fragment crystallizable region (Fc)-fusion proteins, are increasingly used in disease treatment, driving the global market growth. Understanding the pharmacokinetic (PK) properties of ABTs is crucial for their clinical effectiveness. This study investigated the PK profile and tissue distribution of efineptakin alfa, a long-acting recombinant human interleukin-7 (rhIL-7-hyFc), using enzyme-linked immunosorbent assay (ELISA) and accelerator mass spectrometry (AMS). Totally, four rats were injected intramuscularly with 1 mg/kg of rhIL-7-hyFc containing 14C-rhIL-7-hyFc, which was prepared via reductive methylation. Serum total radioactivity (TRA) and serum rhIL-7-hyFc concentrations were quantified using AMS and ELISA, respectively. The TRA concentrations in organs were determined by AMS. Serum TRA peaked at 10 hours with a terminal half-life of 40 hours. The rhIL-7-hyFc exhibited a mean peak concentration at around 17 hours and a rapid elimination with a half-life of 12.3 hours. Peak concentration and area under the curve of TRA were higher than those of rhIL-7-hyFc. Tissue distribution analysis showed an elevated TRA concentrations in lymph nodes, kidneys, and spleen, indicating rhIL-7-hyFc’s affinity for these organs. The study also simulated the positions of 14C labeling in rhIL-7-hyFc, identifying specific residues in the fragment of rhIL-7 portion, and provided the explanation of distinct analytes targeted by each method. Combining ELISA and AMS provided advantages by offering sensitivity and specificity for quantification as well as enabling the identification of analyte forms. The integrated use of ELISA and AMS offers valuable insights for the development and optimization of ABT.